Aktivitelere dayalı yönetim - Özkaynak, Anıl (Fen Bilimleri Enstitüsü, 1997)
Günümüzde, teknolojinin hızla ilerlemesinin yanında, ortaya çıkan yeni üretim, rekabet ve yönetim felsefeleri, işletmelerin rekabet avantajı sağlamak için maliyetlerine odaklanmasını kaçınılmaz kılmıştır. İşletmelerin maliyet yapısındaki değişiklik, işçilik oranları düşerken, genel gider ve teknoloji giderlerinin artması da, geleneksel maliyetleme sistemlerinin yetersiz kalmasına neden olmuştur. Birinci bölümde, yeni üretim çevresinin doğurduğu rekabet ortamı ve bununla ilgili yeni yönetim felsefeleri aktarılmış, bu yeniliklerin Jiıgrıy^LyöQetUm--sistemleri ile ilişkileri açıklanmıştır. Şirketlerin maliyet yapılarındaki değişikliğin yanında yönetimin giderek artan bilgi gereksinimini yeni yönetim muhasebesi sistemlerinin ortaya çıkmasına neden olmuştur. Geleneksel maliyet muhasebesi sistemlerinin eksikliklerine karşılık, ilk defa 1980'lerde, A.B.D. 'de, 4Jrtjjfltelefe--l^^ah~#a%ejy^BdJmae (ADM) adı altında yeni bir maliyet anlayışı ortaya çıkmış ve hızla yaygınlaşmaya başlamıştır. ADM'nin temelinde, kaynakların aktiviteler tarafından tüketildiği, ve bu aktivitelerin işletmenin ürünlerini üret mekte kullandığı gerçeği yatmaktadır. Dolayısıyla kaynakların maliyetleri ürünlere aktiviteler üzerinden taşınmalıdır. Aktiviteler, zamanın nasıl kullanıldığını ve süreçlerin çıktılarını açıklayarak şirketin yaptığı işleri tanımlar. Üçüncü bölümde, ADM'nin ilkeleri açıklanmış, aktivitelere dayalı sistemlerin temeli olan aktiviteler ayrıntılı olarak incelenmiştir. ADM'nin bir işletmede sağlıklı bir şekilde yürütülebilmesi için doğru bir aktivite analizine dayanması gerekir. Dördüncü bölümde, bir işletmenin aktivitelerinin nasıl analiz edilebileceği adım adım anlatılmış, önem verilmesi gereken hususlar belirtilmiştir. Beşinci bölümde aktivitelere dayalı maliyetlerin hesaplama yöntemi ayrıntılı bir şekilde anlatılmış ve küçük bir örnek ile desteklenmiştir. işletmenin aktivite maliyetlerini bulması ile birlikte, birçok maliyet nesnesinin maliyetini kolaylıkla hesaplayabilir duruma gelmiştir. Bu maliyet nesneleri ürün, müşteri, yansanayi, kalite gibi maliyeti hesaplanabilir, şirketin kararlarını etkileyici birimleri kapsar. Bu çalışma kapsamında, altıncı bölümde, birçok işletme için en önemli maliyet nesnesi olan ürünlerin maliyetlerinin hesaplanmasına değinilmiştir. Aktivitelere Dayalı Yönetim(ADY), ADM tekniklerini ve bunlarla elde edilen maliyetleri de kullanarak işletme süreçlerinin incelenmesini ve iyileştirilmesini ve performans ölçümü konularını bir arada işlemektedir. Müşteriye odaklanma, yeniden yapılanma, basitleştirme, kayıpları azaltma, değer katmayan aktiviteleri ortadan kaldırma gibi amaçlar işletmelerin süreç iyileştirme üzerinde önemle durmalarına neden olmuştur. Yedinci bölümde süreç yaklaşımı ile çeşitli süreç iyileştirme teknikleri anlatılmıştır. Sekizinci bölüm, Aktivitelere Dayalı Yönetimi ve süreç yönetiminin önemli bir parçası olan performans göstergelerine ayrılmıştır. Performans göstergeleri, şirketin amaçları ve ulaşmak istediği nokta ile süreçleri ve aktiviteleri arasındaki ilişkiyi kurmak için tanımlanır. Bu bölümde süreçlere yönelik bazı performans göstergeleri önerilmiştir. Dokuzuncu bölüm ADM teknikleri ışığında, aktivitelere dayalı yönetim yaklaşımı ile genel bir yöntem ortaya koymakta ve bu yöntemin bir işletmede ürün maliyetlerinin aktivitelere dayalı olarak hesaplanmasından oluşan bir uygulamayı içermektedir. Aktivite analizi, aktivite maliyetlerinin ve ürün maliyetlerinin hesaplanmasının yürütül düğü ve desteklendiği bu programın teknik bilgileri ve raporları eklerde sunulmuştur. Sonuçlar bölümünde, ADY'nin işletmelere ve yöneticilere getirdiği faydalar anlatılmış ve uygulanmasındaki bazı zorluklara değinilmiştir.

The business world has undergone a major transformation in recent years. Today's customers expect products with high quality, expanded functionality, and low price. To remain competitive, it is crucial for companies not to become complacent. An attempt to keep profit margins stable by increasing price inevitably results in an erosion of market position. The reason for this is that the fundamental factors, driving cost and performance are not addressed by such a strategy. The hallmark of enterprise excellence is a continual commitment to being globally competitive. This requires the never-ending elimination of waste as well as the ability to maintain industry leadership in introducing profitable new products or product variations. The most visible manifestations of successful manufacturers in this new environment are increased automation and computerization, reduced levels of direct labor and inventory, increased attention to product and production planning, and shorter product life cycles. The revolution is based on new manufacturing philosophies such as just-in-time (JIT), total quality management (TQM) and manufacturing resources planning (MRP II), along with judicious implementation of advanced technologies. To stay ahead of the competition, companies must have information to provide the necessary understanding of the factors they can influence. Management must place pressure on the entire organization for measurable cost reduction and productivity gains. Cost must not be allowed to get out of the line in the first place. An important reason that a company's cost becomes non-competitive is that conventional cost accounting systems distort product costs and do not highlight productivity improvement opportunities, thus leading to poor decisions. Competitive advantage demands that companies be able to provide accurate answers to the following questions: 1. What are the influenceable costs and profits for each major product line and customer? 2. What are the cost behavior patterns of each activity, including its capacity, and how much can volume be increased or decreased before costs change? 3. What is the waste (non-value-added) component of cost and what are the best practices for an activity? 4. How does overhead cost vary with changes in business? What costs are avoidable if volume declines? 5. How do the current cost structure, capacity utilization, and non-financial performance trends compare with those of the competitors'? 6. How can low cost be designed into new and existing products? Cost management based on this sort of activity information is the heart of the new management information systems that help managers answer these critical questions. Activity based management (ABM) profiles a company in terms of the cost and performance of its specific activities. In light of the revolution taking place in the business world, one would expect to see significant changes in accounting. After all, the conventional cost accounting systems were designed for a prior era when direct labor and materials were the predominant factors of production, technology was stable, overhead activities supported the production process, and there was a limited range of products. Traditional cost accounting systems do not, however, provide adequate information to identify the causes of the cost, and they do not provide a clear picture of how costs and profits change as an activity volume moves up or down. Thus they are not particularly helpful to managers who must evaluate sales, marketing, or manufacturing activities that involve different levels of activity. The activity-based management approach to cost management breaks down an organization into activities. An activity describes what an enterprise does - the way time is spent and the outputs of the process. The principal function of an activity is to convert resources (materials, labor and technology) into outputs. XI Activity-based management is a powerful tool for managing the complex operations of a business through a detailed assessment of its activities. Activity-based management generates cost and production information in a manner that drives continual improvement and total quality. Continual improvement and total quality control are facilitated by treating each activity as a process and identifying the source of cost rather than focusing on symptoms. The basic element of activity-based management is the activity. An activity is a combination of people, technology, raw materials, methods and environment that produces a given product or service. Examples of activities include: Closing a sale, producing marketing material, assembling the final product, billing the customer. Activities are defined in the broadest sense to include both manufacturing processes and the group of activities that support the manufacturing process. Costing based on activities therefore provides equal visibility for support and production costs. The basis of an activity-based management system is formed out by an activity analysis. Activity analysis identifies the significant activities of an enterprise in order to establish a basis for accurately determining their cost and performance. Activity analysis decomposes a large complex organization into elemental activities that are understandable and easy to manage. The explicit management of activities gives an enterprise a better insight into how resources are employed and whether the activity contributes to the achievement of corporate objectives. This approach is in contrast to today's accounting systems, which provide visibility of total resources employed by each organizational unit, but not of what the unit does. The next step in building an activity-based management system is calculating the activity cost to supply a resource for further calculation of cost objectives like product, customer, supplier, distribution channel or even quality. Activity cost is derived by tracing the cost of all significant resources to perform an activity. Activity cost is expressed in terms of a measure of activity volume by which the costs of a given process vary most directly. For example, the cost of scheduling production orders may be expressed as a cost per production order. Measuring activity effectiveness requires knowing the amount of output (activity volume) as well as the activity cost. In activity accounting, the execution of an activity is understood to consume resources. Products consume activities. Product cost is determined through a bill of activities that itemizes the activities and the quantity of each activity consumed in XII manufacturing a specific product. An activity-based product cost is derived by summing the cost of ail activities in the bill of activities. Product costing is enhanced by more direct tracing of support costs, which have traditionally been lumped into overhead and allocated to products. Another issue in activity-based management is the business process. A business process analysis determines the interdependences among activities. Insight into these interrelationships provides visibility of the events that trigger the business process. By controlling the initiating event, a company can reduce or eliminate the cost of ail subsequent activities. Today's cost accounting systems do not portrait the interrelationships among activities. Understanding activity relationships facilitates the streamlining of business processes by identifying redundant and unnecessary activities, which increase cost without any corresponding benefit in the marketplace. The entire business process can therefore be restructured to reduce cost and improve efficiency. The procedure for analyzing a business process is to determine the sequence of activities by following the flow of information from one activity to another. The information flows represent inputs and outputs and constrain an activity. Until information needed to perform an activity is delivered correctly and at the appropriate time, an activity cannot be effectively performed. Business process analysis facilitates the evaluation of alternative organizational structures. It is often best to organize people and machines into natural groups and around processes or information flows. Performance measures are the financial and operational statistics used to gauge the performance of a company. Under activity-based performance measurement, each activity is analyzed to determine how effectively the work is being performed as gauged by key performance measures such as quality, cost, and time. Each performance measure is simply a different attribute of an activity. Performance measures provide an important perspective on how effectively the activity helps to achieve enterprise objectives. Performance measures are interrelated. A reduction in time, for example, will impact cost, quality, and flexibility because it impacts the performance of activity. A key to effective cost management is the implementation of changes that simultaneously improve multiple dimensions of performance. The application discussed in this thesis is based on a methodology which is a logical mix of literature surveys and experience on this topic. Some assumptions xiii had to be made considering the real life and the data availability in the firm in which the application work is done. Especially the accounting data were hard to gather in the desired form due to the lack of a relational database on accounting. The methodology is applied to an electric motor manufacturer, analyzing all the processes of the firm. The activity-based management application is supported by an ABM software developed by the author and used in three activity-based management user sites yet. The software is built on a database using user-friendly interfaces, which makes data entry as easy as possible. Several reports produced by the system can be seen in the Appendixes. The key advantage of activity-based management is that it provides a more accurate way to look at overhead and indirect costs, including those generated off the factory floor and not typically factored into product-by-product cost calculations- activities such as marketing, distribution and maintenance. It supports also a customer focus by helping a company measure and manage two types of activities: Value-added activities and non-value-added ones, those that should be reduced and/or eliminated.
Aktivity-based management
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1997
Keywords: Aktiviteye dayalı muhasebe; Maliyet; Rekabet; Yönetim sistemleri; Üretim; Activity based costing; Cost; Competition; Management systems; Production